2021
DOI: 10.3390/ijerph182312657
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Analysis of the Stigma Surrounding Type 2 Diabetes in Colombia

Abstract: Type 2 diabetes is a global epidemic, and many people feel stigmatized for having this disease. The stigma is a relevant barrier to diabetes management. However, evidence in this regard is scarce in Latin America. This study aimed to analyze the level of stigma surrounding type 2 diabetes in the Colombian population and its relationships with sociodemographic, clinical, psychosocial variables and behaviors related to management of the disease (self-management behaviors). This cross-sectional study included 501… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 61 publications
0
12
1
1
Order By: Relevance
“…While research on this topic is limited, existing studies have reported that stigma reduces the diabetes management self-efficacy levels of people with diabetes not only directly but also by lowering their selfesteem. 17,33,34 A previous study used a model to determine how self-stigma affected the self-care behaviors of people with diabetes regarding diabetes management, where both the direct effect of the variable and its effect mediated by self-esteem were investigated. The authors demonstrated that self-stigma affected the patient's activation both directly and under the mediation of self-esteem.…”
Section: (mentioning
confidence: 99%
See 1 more Smart Citation
“…While research on this topic is limited, existing studies have reported that stigma reduces the diabetes management self-efficacy levels of people with diabetes not only directly but also by lowering their selfesteem. 17,33,34 A previous study used a model to determine how self-stigma affected the self-care behaviors of people with diabetes regarding diabetes management, where both the direct effect of the variable and its effect mediated by self-esteem were investigated. The authors demonstrated that self-stigma affected the patient's activation both directly and under the mediation of self-esteem.…”
Section: (mentioning
confidence: 99%
“…The authors demonstrated that self-stigma affected the patient's activation both directly and under the mediation of self-esteem. 17 In a study carried out with 501 people with T2DM, Pedrero et al 34 investigated the mediating role of psychosocial variables in the relationship between perceived stigma and self-management behaviors in people with diabetes, and they reported that self-esteem had a mediating role in this relationship. In similarity to the results of other studies, in this study, it was determined that the effect of perceived stigma in the patients on their diabetes management self-efficacy decreased when the variable of self-esteem was added to the model.…”
Section: (mentioning
confidence: 99%
“…Diabetes-related stigma was found to have both a direct [6,20] and an indirect effect [6] on patient activation; a concept that involves patient's knowledge, skills and engaging in behaviors conducive to the management of their illness. Psychologically, stigma lowers self-efficacy and self-esteem, and increases stress in diabetics , [10] which leads to engagement in less healthy behaviors, and as a result glycosylated hemoglobin, is found to be adversely affected by diabetes-related stigma. [7][8][9] There is urgent need for research in the area of stigma [19] that includes documenting the magnitude and nature of diabetesrelated stigma, comparing stigma in different settings, and identifying its determinants.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that diabetes-related stigma affects the course and outcome of diabetes including hindering self-care , [6] having an effect on glycemic control [7][8][9] as well as psychological effects. [10] Weiss and Ramakrishna [11] have formulated a definition specific for health-related stigma: "a social process or related personal experience characterized by exclusion, rejection, blame, or devaluation that results from experience or reasonable anticipation of an adverse social judgment about a person or group identified with a particular health problem." Link and Phelan [5] characterize 3 major forms of discrimination, with varying degrees of severity; direct discrimination, structural discrimination and insidious discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…Muitas pessoas com DM sentem-se julgadas, inclusive por profissionais de saúde, como se fossem "preguiçosas" e "responsáveis pela doença" (49,51). Esse estigma está negativamente correlacionado à autoestima, ao autocuidado e a percepção da qualidade do serviço de saúde recebido (50,52,53). Devemos, portanto, Reconhecer que a hiperglicemia na gestação tem impactos duradouros na vida da mulher, e oferecer seguimento e acompanhamento criteriosos, é essencial para melhorar a assistência à saúde.…”
Section: Assim Como Emunclassified